Using traditional Chinese medicine to manage your emotional health how herbs, natural foods, and acupressure can regulate and harmonize your mind and body - Zhang, Yifang, 1959- (New York Better Link, 2013)
Details the natural solutions offered by Chinese medicine for treating and managing emotional problems, suggesting such lifestyle changes as using acupressure, exercising with exposure to sunlight, and adding herbs to the diet.
Includes bibliographical references (p. 152)
DD Knowledge (12.09.13)
Keywords: Medicine, Chinese -- Popular works; Mental health -- Popular works